Aerosol-spray metal phosphide microspheres with bifunctional electrocatalytic properties for water splitting. Issue 11 (28th February 2018) - Jia, Henglei; Jiang, Ruibin; Lu, Wenzheng; Ruan, Qifeng; Wang, Jianfang; Yu, Jimmy C.
Abstract : Aerosol spray is used to synthesize metal phosphide microspheres to act as bifunctional catalysts for overall water splitting. Abstract : Transition metal phosphides have sparked considerable interest as electrocatalysts owing to their excellent catalytic activities towards water splitting. However, the development of a general strategy for the preparation of metal phosphides has remained challenging. In this work, we demonstrate a two-step, aerosol spray-based strategy for the synthesis of various mesoporous monometallic and multimetallic phosphide microspheres. Four monometallic (FeP, CoP, Ni2 P, and Cu3 P), one bimetallic (Co6 Ni4 P5 ) and one trimetallic (Co4 Ni3 Cu2 P10 ) phosphide samples are successfully prepared, suggesting the generality of our method. In addition, the CoP sample is found to be an excellent material for the hydrogen evolution reaction over a wide pH range through the introduction of corrosion-resistant Cr2 O3 . On the other hand, its catalytic activity can be switched to the oxygen evolution reaction in combination with Fe2 O3 . The overpotential for the oxygen evolution reaction to generate a current density of 10 mA cm −2 is as low as 302 mV. This activity can be maintained for at least 50 h. More importantly, a two-electrode electrolyzer constructed from 10% Cr–CoP and 30% Fe–CoP samples delivers a current density of 100 mA cm −2 at a cell voltage of merely 1.67 V, showing the use of these cost-effective materials for bifunctional water splitting.